5 years old and stressed out ; Takbo, vendors, takbo! ; Sailing, Pinoy style [videorecording] - Lazaro, Cheche (Quezon City Probe Productions)
Tackles education in the pre-school; street vendors; and the Parao, a pre-historic fishing vessel and a means for transportation.
5 years old and stressed out (17 min.) -- Takbo, vedors, takbo! (10 min.) -- Sailing, Pinoy style (12 min.)
VHS.
Keywords: Education, Preschool -- Philippines; Peddlers and peddling -- Philippines; Boats and boating -- Philippines